Investigation on the botnets activities - HAN Xin-hui1; GUO Jin-peng1; ZHOU Yong-lin2; ZHUGE Jian-wei1; ZOU Wei1 (Tongxin xuebao)
Botnets have become the first-choice attack platform for the network attackers to launch distributed denial of service attacks,steal sensitive information and send spam.They have raised serious threats to normal operation of the Internet and the benefits of the Internet users.The investigation on the wild botnets activities is the necessary for the fur-ther monitering and countermeasure against world-wide botnets.Based on the investigation and analysis on tracking re-cords of 1 961 wild botnets,it shows the statistical results of botnet activities,including amount of botnets,command and control channel distributions,botnet size and end-host distributions,and various types of botnet attack activities.